2006
DOI: 10.1097/01.qai.0000179455.01068.ab
|View full text |Cite
|
Sign up to set email alerts
|

Removing Barriers to Knowing HIV Status

Abstract: Same-day HIV testing in community settings seems to be acceptable in sub-Saharan Africa. Barriers to HIV testing are often logistic and can be overcome with community-based strategies. These strategies need to be refined to address the needs of those not using mobile testing services.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
63
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 139 publications
(68 citation statements)
references
References 7 publications
4
63
0
Order By: Relevance
“…Despite the widespread availability of VCT tests through project-supported static clinics, uptake of HIV testing was low. Barriers to HIV testing are often logistical and can be overcome with community-based strategies [15]. Evidence suggests that community-based VCTs are preferred over static or health facility-based clinics for HIV testing [15] [21] [22] as was observed in our study with a dramatic increase in the uptake of HIV testing during Vivek months.…”
Section: Discussionsupporting
confidence: 60%
See 2 more Smart Citations
“…Despite the widespread availability of VCT tests through project-supported static clinics, uptake of HIV testing was low. Barriers to HIV testing are often logistical and can be overcome with community-based strategies [15]. Evidence suggests that community-based VCTs are preferred over static or health facility-based clinics for HIV testing [15] [21] [22] as was observed in our study with a dramatic increase in the uptake of HIV testing during Vivek months.…”
Section: Discussionsupporting
confidence: 60%
“…HIV testing is the gateway for HIV prevention as early initiation of ART and safer sexual behaviour could potentially reduce transmission together with other interventions [6]- [8] [12]. As voiced in earlier literature, addressing individual and contextual barriers and increasing demand facilitates HIV testing uptake [6] [15] [19] [20].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Participants who reported not testing previously were most likely to report fear as the main factor preventing them from accessing testing. Although the survey instrument did not determine the source of such fear, research in sub-Saharan Africa has indicated that despite treatment availability, the potential for a positive HIV test result is a significant barrier to testing (MacPhail et al 2008a, b;Morin et al 2006). Our previous research with South African adolescents has shown an overwhelming fear of the psychological impacts of learning that one is HIV positive, with many believing that this will lead to suicide and a more rapid decline to AIDS and death (MacPhail et al 2008a).…”
Section: Discussionmentioning
confidence: 99%
“…In Malawi, Smith, and Watkins (2005) found that women were more worried about getting HIV from unfaithful husbands, while men were more worried about getting HIV from their extramarital partners. Other studies from the region suggest that women who suspect that their main partner has other sexual partners may be more inclined to test for HIV (Luseno & Wechsberg, 2009; Morin et al, 2006). Few studies, however, have obtained data from couples, which could provide clarifying information regarding the effect of perceived risk on both partners’ testing behaviors.…”
Section: Introductionmentioning
confidence: 99%